Pengaruh Brand awareness Ricky Harun di Instagram, Brand awareness, dan Harga Promo Terhadap Keputusan Pembelian Brand Kahf (Studi Kasus Pada Mahasiswa FEB Unisma) - Althaf Ariq Luthfi Noufal; N. Rachma; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study investigates how brand awareness  endorsement, brand awareness, and promotional pricing influence purchasing decisions toward Kahf grooming products among university students. A quantitative explanatory approach was employed using survey data collected from 105 male students of the Faculty of Economics and Business at Universitas Islam Malang. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects. The findings demonstrate that brand awareness  credibility and attractiveness, strong brand awareness, and competitive promotional pricing significantly affect purchasing decisions. Among the variables tested, brand awareness shows the strongest predictive power. The results highlight the importance of integrating brand awareness  marketing strategies with consistent brand-building and value-oriented promotional pricing to strengthen consumer decision-making. This research contributes to digital marketing literature by providing empirical evidence from an emerging market context. Keywords: Brand awareness  Marketing, Brand Awareness, Promotional Strategy, Consumer Behavior, Purchasing Decision